2018
DOI: 10.1093/mnras/sty1893
|View full text |Cite
|
Sign up to set email alerts
|

Differential interferometry of the rapid rotator Regulus

Abstract: We analyse interferometric data obtained for Regulus with AMBER (Astronomical Multi-BEam combineR) at high spectral resolution (λ/δλ ≈ 12000) across the Brγ spectral line. The study of the photocentre displacement allows us to constrain a large number of stellar parameters -equatorial radius R eq , equatorial velocity V eq , inclination i, rotation-axis position angle P A rot , and flattening -with an estimation of gravity-darkening coefficient β using previously published theoretical results. We use the Simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(47 citation statements)
references
References 46 publications
(75 reference statements)
3
44
0
Order By: Relevance
“…By applying our new continuous and multilayer MOLsphere approach, we present first in this section the results of three published stars, BK Vir, α Boo, and SW Vir (where we compare, for these latter, the results of our multilayer approach with the results from the bi-layers approach, using the values given in Table. B1 and computations with PAMPERO), then we present the new results of four evolved stars (including one Mira observed for two epochs), γ Cru, λ Vel, α Sco and W Hya (Fig.D1 to D8). We determine the uncertainties of the six free parameters (T0, N0, ζT, ζN, R mol,0 , & R mol,end ) that we presented in Section 4.2, using the same method that was used for the other model, which is dedicated to Hot Active Stars (SCIROCCO; Hadjara et al 2014;Hadjara 2015;Hadjara et al 2018), when the χ 2 -minimization was used, after localizing the global minimums by using a large grid of six free parameters. The results are given in Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying our new continuous and multilayer MOLsphere approach, we present first in this section the results of three published stars, BK Vir, α Boo, and SW Vir (where we compare, for these latter, the results of our multilayer approach with the results from the bi-layers approach, using the values given in Table. B1 and computations with PAMPERO), then we present the new results of four evolved stars (including one Mira observed for two epochs), γ Cru, λ Vel, α Sco and W Hya (Fig.D1 to D8). We determine the uncertainties of the six free parameters (T0, N0, ζT, ζN, R mol,0 , & R mol,end ) that we presented in Section 4.2, using the same method that was used for the other model, which is dedicated to Hot Active Stars (SCIROCCO; Hadjara et al 2014;Hadjara 2015;Hadjara et al 2018), when the χ 2 -minimization was used, after localizing the global minimums by using a large grid of six free parameters. The results are given in Tab.…”
Section: Resultsmentioning
confidence: 99%
“…A MOLspheric temperature-density study of dust around evolved stars, especially in the L, M and N bands with the new instrument VLTI/MATISSE (Lopez et al 2014) would be very interesting too. For future work we would use the Markov Chain Monte Carlo (MCMC) method on the free parameters and their uncertainties for our PAMPERO model (as we did in Hadjara et al 2018). Prior to this, we first have to find a technical solution on how to efficiently use the MCMC method for large intervals of the six free parameters within reasonable calculation times.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lucy (1967) found 𝑇 eff ∝ 𝑔 0.08 eff for the gravity darkening effect, when considering a convective envelope (i.e., dropping the assumption of radiative equilibrium). More generally, this effect follows the relation 𝑇 eff ∝ 𝑔 𝛽 eff , where the exponent 𝛽 is lower than 0.25 (e.g., van Belle et al 2006;Monnier et al 2007;Hadjara et al 2018;. This means that the von Zeipel theorem, as originally stated, is likely to overestimate the difference of temperature between the pole and the equator.…”
Section: Stellar Rotationmentioning
confidence: 94%
“…18-0.25 (van Belle et al 2006;van Belle 2012;Monnier et al 2007;Che et al 2011;Hadjara et al 2018;Domiciano de Souza et al 2018) with the most likely value of 0.21 (van Belle 2012). The theoretical study of Espinosa Lara & Rieutord…”
mentioning
confidence: 99%
“…with β = 0.25. However, interferometric studies of stellar spectral classes of F to B suggested that the β parameter is typically in the range of 0.18-0.25(van Belle et al 2006;van Belle 2012;Monnier et al 2007;Che et al 2011;Hadjara et al 2018;Domiciano de Souza et al 2018) with the most likely value of 0.21 (van Belle 2012). The theoretical study of Espinosa Lara & Rieutord (2011) suggested that the value of β is a function of the rotational rate of the star.…”
mentioning
confidence: 99%